Water Blister in Teak - Bakshi, B. K.; Boyce, J. S. (Indian Forester, 1959)
Water blister disease in teak is noticed in certain plantations along rivers in Nilambur, Kerala state. It is characterized by exudation of light yellow sap in large quantity from the stem near ground level. As the sap dries up, it leaves a blackish discolouration on the stem. The cause appears to be physiological. In winter when trees become leafless, transpiration is cut down. Under conditions of high temperature and soil moisture, root pressure builds up, forcing the sap to collect in the crevice of the wood, developed as a result of shake, in increasing quantity under pressure, till it finds its release through the thin bark. Though the diseased trees are not killed they become damaged in the wood and may be removed during improvement fellings and thinnings. It is advisable to avoid planting teak in very moist sites where water blister develops.